Engaging High Water Users in Water Conservation #1: High Water Users’ Experiences and Perceptions of Water - Pei-wen Huang; Alexa J. Lamm (EDIS)
Florida has an abundance of water, but still faces an increased pressure on water resources because of a growing population, prosperous tourism, and an active agricultural industry. This 5-page fact sheet is the first in a series discussing how Extension can improve high water users' engagement in water conservation by focusing on high water users' characteristics, experiences with water issues, and perceptions of water. Written by Pei-wen Huang and Alexa J. Lamm, and published by the Department of Agricultural Education and Communication, July 2016.